2017
DOI: 10.35609/jber.2017.2.3(3)
|View full text |Cite
|
Sign up to set email alerts
|

Micro, Small and Medium Enterprises (MSMEs) Coaching Program

Abstract: Objective - This study aims to examine and analyze micro small and medium enterprises (MSMEs) coaching program and to obtain an empirical evidence regarding the effect of MSMEs coaching program on the quality of financial statements. Methodology/Technique - This study was conducted using quantitative descriptive method and statistical analysis using a sample of 50 entrepreneurs in several MSMEs coaching program institutions in Pontianak, West Kalimantan. Findings - The result shows that all objectives of MSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It was also found that support from various parties was needed to improve the performance of SMEs in several countries. Hamzani & Achmad (2017); Lekmat & Intaragasam (2019) and Kurdve et al (2020) stated these supports could come from academicians through coaching, training and mentoring, financial institutions with their soft financial support schemes, institutions or companies with their CSR schemes in the forms of partnership, coaching, and development, and the government through policies which were conducive for and favorable to SMEs.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It was also found that support from various parties was needed to improve the performance of SMEs in several countries. Hamzani & Achmad (2017); Lekmat & Intaragasam (2019) and Kurdve et al (2020) stated these supports could come from academicians through coaching, training and mentoring, financial institutions with their soft financial support schemes, institutions or companies with their CSR schemes in the forms of partnership, coaching, and development, and the government through policies which were conducive for and favorable to SMEs.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to Hamzani and Achmad [28], training programs also assist clients in developing their learning capabilities and enhancing their educational performance, thus ultimately resulting in better socio-economic outcomes. Additionally, training programs are also important in boosting satisfaction and confidence level among households and microentrepreneurs [29].…”
Section: Microfinance Non-financial Servicesmentioning
confidence: 99%